PEMBUATAN APLIKASI PENJEMPUTAN SAMPAH ANORGANIK (DTRASH) MENGGUNAKAN METODE USER CENTERED DESIGN (UCD) - Olethea Farah Utari; Humaini, Irfan; Ira Windarti (Jurnal Teknik dan Science, 2024)
Inorganic waste is waste that is no longer used and is difficult to decompose, examples of inorganic waste can easily be found in everyday life such as plastic, bottles, and bulbs. Puri Bojong Lestari Housing is a housing complex located in Pabuaran Village, Bojonggede District, Bogor Regency.  Inorganic waste pick-up is often problematic because communication between garbage pick-ups and consumers is often constrained. An alternative solution to this problem the residents of puri bojong lestari housing feel the need for an application, with this application, the officers picking up waste in picking up waste to residents becomes easier. The developed application is based on Android.  The results of the implementation of the design using the User Centered Design (UCD) method with this method are expected to be able to know the function of the system in one use, designing the system using firebase databases to facilitate the authentication process. The design method used is an object-oriented approach with Unified Modelling Language (UML) modeling and implemented with the Java programming language. This inorganic garbage pick-up application is named (DTrash). The results of the trial showed that the application was running lane ar. Results of user trials through 100 respondents of application users, obtained results percentage of 88.88% of users Agreed to the functionality and benefits of the application for users.